MicroRNA-200c Promotes Suppressive Potential of Myeloid-Derived Suppressor Cells by Modulating PTEN and FOG2 Expression - Mei, Shiyue (PLoS One, 2015)
Myeloid-derived suppressor cells (MDSCs) constitute one of the major populations that potently suppress anti-tumor immune responses and favor tumor growth in tumor microenvironment. However, the mechanism(s) regulating the differentiation and suppressive function of tumor-associated MDSCs remain(s) unclear. Here, we identified a microRNA-200c (miR-200c), whose expression was dramatically induced by tumor-derived factors. Meanwhile, we also demonstrated that GM-CSF was a main inducer of miR-200c in tumor environment, and miR-200c in turn promoted the expansion and immune suppressive activity of MDSCs via targeting phosphatase and tensin homolog (PTEN) and friend of Gata 2 (FOG2), which can lead to STAT3 and PI3K/Akt activation. Finally, we examined in vivo suppressive function of miR-200c transfected MDSCs and found that miR-200c could remarkably promote tumor growth via modifying MDSCs. Thus, GM-CSF induced miR-200c in tumor environment plays a critical role in governing the expansion and functions of tumor-associated MDSCs and serves as a potential target in immunotherapy against tumor.